Pelayanan Publik di Sektor Pendidikan Tinggi Selama Masa Pandemi Covid-19 - Dhita Widya Putri; Adinda Marhietta; Mochammad Ibrahim Zainal (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
COVID-19 outbreak has changed certain human habits and activities. In higher education environment, there were transformation and adaptation in terms of technology usage. The Agency for Higher Education for Region III, Jakarta Province is a working unit under the Ministry of Education, Culture, Research, and Technology which has the task of facilitating the improvement of the quality of higher education. During the pandemic, they have been making various efforts and ensuring that the public services are still running well. By using descriptive qualitative methods, in-depth interviews, and observations, this study examines the process of public service through 3 stages of change from Tikson; Unfreeze, Change, and Refreeze. Keywords: public services, higher education, COVID-19 pandemic